Можливості та перспективи соціологічного теоретизування щодо політико-ідеологічної ідентифікації особистості - Агаларова, Карина Адільївна (Харківський національний університет ім. В. Н. Каразіна, 2015)
У статті аналізуються теорії, які пояснюють феномен політико-ідеологічної ідентифікації особистості. Підкреслюється міждисциплінарний характер дослідження цього феномену. З огляду на багатовимірність політико-ідеологічної ідентифікації, наголошується на необхідності теоретичного синтезу концептів ідентифікації та ідентичності, які існують у психологічному, соціологічному, соціально-психологічному та інших наукових дискурсах. Наводяться результати авторських напрацювань у цьому напрямку, зокрема спроби теоретичного синтезу ідей диспозиційної концепції відомого російського соціолога В. Ядова, наукового доробку українського дослідника О. Резніка щодо тривимірної моделі українського політичного простору та соціокультурного підходу до аналізу політико-ідеологічної ідентифікації особистості. Зазначається, що такий "синтетичний" підхід та здійснене на його основі емпіричне соціологічне дослідження дозволили дійти висновку, що політико-ідеологічні ідентичності постійно реконструюються у відповідності до змін соціально-політичних контекстів та трансформації ціннісних орієнтацій особистості. Робляться висновки щодо необхідності побудови концептуальної моделі, яка б відігравала роль зразка для емпіричних досліджень політико-ідеологічної ідентифікації особистості. Розробка такої моделі має здійснюватися на основі соціокультурної теорії множинних нестійких соціально-ідентифікаційних станів особистості, яка у поєднанні із зазначеними вище концепціями дозволяє акцентувати на процесуальності, діяльнісності та символічній укоріненості ідентичностей.

The article is devotes to the theoretical synthesis of theories, which explain the phenomenon of politicalideological identification. In social science there is great deal of identification theories, that is determined, first of all, by interdisciplinary character of this problem. Despite of different theoretical approaches, each separate theory can't fully explain peculiarities of process of individual identity' formation, including political-ideological identification. Regarding this fact there is a strong need in theoretical synthesis of theories, which explain explored phenomenon. Theoretical synthesis of processing of this problem allowed: to apply ideas of russian sociologist Yadov's disposition concept to analysis of processes of political-ideological identification; to adopt proposed tridimensional model to Ukrainian political space, regarding theoretical modification of Ukrainian researcher Reznik. Also to make conclusion that model of identity's political-ideological identification needs to be formed taking into account behavioral aspect of political-ideological identification and category "political subjectivity"; regarding methodology of socio-cultural approach to make conclusion that political-ideological identities are constantly reconstructed in accordance with changes in social-political contexts. We can assume that, as political self-consciousness of individual ideological values, forms specific political positions, political-ideological identification has multifold, multilevel structure. That's why we need appropriate conceptual model, which would demonstrate this specificity, establish objective, conceptual and methodological connections regarding theories reviewed above, take a role of the sample for empirical researches of political-ideological identification. We think that development of this model should be conducted basing on socio-cultural theory of numerous non-stable social-identificational conditions of identity, which, in combination with concepts stated above, allows to accentuate processing, activity and symbolical inculcation of identities in modern conditions.
Opportunity and perspectives of the sociological theoretization about person’s political and ideological identification
Keywords: диспозиційна структура особистості; ситуативна ідентичність; політична суб'єктність; стійка ідентичність; dispositional structure; political subjectivity; situational identity; stable identity